(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: Mentor-mentee program is essential for mentees’ development. The objective of this paper was to investigate mentees’ perceptions on their mentors. Methods: A questionnairesurvey among all-50 clinical-medical students who mentored by 16 faculty members at Widad University College(WUC)Malaysia, was conducted in 2019.A standardized-questionnaire that examined the mentorship-roles, communication-frequencies, mentor-mentee-relationships and mentoring-effectiveness was used. Relationship was measured by a 4-point scale against each of satisfaction, importance, support, and impact while effectiveness was measured using 0-5 scale on 11-behavioral-skills. Results: Response rate was 92%; only 17% mentees perceived, their mentors played all five mentorship-roles while 30% played only one role. Though 41% mentees had ≥6 communications per-semester with mentors, one year-5 mentee had no-communication at all. Over 16 mentor-mentee relationship and 55 mentoring-effectiveness scores, the mean relationship and effectiveness score was 12.03(75%) and 37.45(72%) respectively. Mentees expected more communication-sessions and their contributions to be acknowledged. Conclusion: Mentor-mentee program at WUC revealed 75% and 72% respectively in mentormentee- relationship and mentoring-effectiveness, which is good. However, faculty needs to play more mentorship-roles and acknowledged mentees’ contributions. Addition of portfolio and reflective-writing in the curriculum will benefits in monitoring mentees’ development. Educational managers should pay attention to this and adequate training of mentors to fulfil the mentees’ needs. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.840-847